In the field of gravity: the structure and elements of public power - A. A. Larichev; О. A. Kozhevnikov (Правоприменение, 2024)
The subject of this study includes the approaches to the definition of the category of public power, as well as variants of its structure and elements.The goal of the article is to compare the experience of various jurisdictions, including Russia, in the construction of public power, and to establish contemporary determinants of its structure and consequences of its expansion. Comparative and formal legal methods are mainly used to produce the results of the research.Main results. The authors notice, that in most jurisdictions legislative attempts to give a definition of the structure of public power and to indicate the circle of its subjects entail indeterminacy and the inevitable expansion of the corresponding subject composition. That, apparently, is caused by the dynamics of the functions of public power, which determines the institutional evolution. It is not a secret that since the beginning of the 20th century the volume of functions entrusted to the state, and accordingly, to its bodies of power and management, has grown significantly. Since there are plenty of tasks and functions that correspond to the public interest, the state involves in the process not only its structural units the bodies of state power, but also private subjects. Private entities, mobile and adapted to competition and social-economic changes, are capable of more effective implementation of tasks, performance of functions and provision of services that can be administratively outsourced. In the USA, for example, this phenomenon becomes so large-scale that it sometimes referred to as "mixed administration" in academic literature. In Russia, the possible forms and limits of the involvement of private subjects in the implementation of public tasks continue to remain under question, both from a theoretical and a practical point of view.Conclusions. Formation of the structure of public power is influenced by historical, sociocultural, and legal features of the development of states. In most jurisdictions the basis ("locus of gravity") of public power is comprised of the authorities (both of state and municipal level), in the orbit of which, depending on the need for the implementation of public functions, other subjects of law – public and private companies and even NGO’s – are included. Therefore, functional unity is the main determinant of the structure of public power mechanism.